A shallow-water system with vanishing buoyancy. Issue 10 (26th July 2020) - Kalisch, Henrik; Teyekpiti, Vincent
ABSTRACT: In this work, a shallow-water system for interfacial waves in the case of a neutrally buoyant two-layer fluid system is considered. Such a situation arises in the case of large underwater lakes of compressible liquids such as CO 2 in the deep ocean which may happen naturally or may be man-made. Depending on temperature and depth, such deposits may be either stable, unstable or neutrally stable, and in the current contribution, the neutrally stable case is considered. The motion of the long waves at the interface can be described by a shallow-water system which becomes triangular in the neutrally stable case. In this case, the system ceases to be strictly hyperbolic, and the standard theory of hyperbolic conservation laws may not be used to solve the initial value or even the Riemann problem. It is shown that the Riemann problem can still be solved uniquely using singular shocks containing Dirac delta distributions traveling with the shock. We characterize the solutions in integrated form, so that no measure-theoretic extension of the solution concept is needed. Uniqueness follows immediately from the construction of the solution. We characterize solutions in terms of the complex vanishing viscosity method, and show that the two solution concepts coincide.